2011
DOI: 10.1186/1471-2180-11-187
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the cage system and colonisation of Salmonella Enteritidis on the microbial gut flora of laying hens studied by T-RFLP and 454 pyrosequencing

Abstract: BackgroundIn the EU conventional cages for laying hens are forbidden beginning in January 2012, however concerns about a higher transmission rate of Salmonella in alternative cages systems have been raised. The extent to which cage systems may affect the intestinal microbiota of laying hens is not known, and different microbiota may demonstrate different resistance towards colonization with Salmonella. To investigate this, ileal and caecal samples from two experimental studies where laying hens were inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 29 publications
7
50
1
4
Order By: Relevance
“…In addition, the most interesting finding was that the island and inland groups had distinct gut microbiota profiles. The butyric acid-producing genus Butyricimonas of the phylum Bacteroidetes was highly abundant in inland subjects [25, 26]. Butyric acid is a short-chain fatty acid and a product of the fermentation of dietary fiber by the gut microbiota [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the most interesting finding was that the island and inland groups had distinct gut microbiota profiles. The butyric acid-producing genus Butyricimonas of the phylum Bacteroidetes was highly abundant in inland subjects [25, 26]. Butyric acid is a short-chain fatty acid and a product of the fermentation of dietary fiber by the gut microbiota [27].…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiology of Gallus gallus has received considerable prior attention, however, the majority of experiments have been performed with broilers, and the gut microbiota composition in egg laying hens has been characterised much less frequently [1-4]. The reason why the majority of experiments have been performed in broilers is quite clear, as the gut microbiota, especially its altered development, significantly reduces the profitability of broiler producers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other investigators have attributed a greater risk of Salmonella infection to cage-based housing, especially when rodent population densities are high (Huneau-Salaün et al, 2009;Snow et al, 2010;Van Hoorebeke et al, 2010b). Moreover, some studies have concluded that no significant differences in the prevalence of either environmental contamination or fecal shedding of Salmonella in laying flocks were evident between cage and cage-free systems (Siemon et al, 2007;Jones et al, 2012) or between conventional and enriched cage systems (De Vylder et al, 2009;Nordentoft et al, 2011;Van Hoorebeke et al, 2011). The current study sought to expand the implications of these earlier results by monitoring horizontal transmission of Salmonella Enteritidis infection among hens in conventional and enriched colony cage systems.…”
Section: Discussionmentioning
confidence: 79%